A sustainable livelihood approach to poverty reduction : an empirical analysis of Mizoram, the Eastern extension of the Himalaya /: an empirical analysis of Mizoram, the Eastern extension of the Himalaya. ([2017]) - Sati, Vishwambhar Prasad; Vangchhia, Lalrinpuia
No abstract available